Intravenous Lobular Capillary Hemangioma in the Renal Vein Mimicking Renal Cancer - Keisuke Ueki; Hideaki Ito; Takafumi Kabuto; Yasuharu Kaizaki; Ishida Takuya; Tadahiro Kobayashi (IJU Case Reports)
ABSTRACT Introduction Lobular capillary hemangioma is a benign tumor that commonly occurs in the skin and mucous membranes. A lobular capillary hemangioma that occurs within blood vessels is called intravenous lobular capillary hemangioma. In this report, we report the fifth case of intravenous lobular capillary hemangioma originating from a renal vessel. Case Presentation A 68‐year‐old man was diagnosed with right renal cell carcinoma with right renal vein tumor thrombus on computed tomography examination for asymptomatic aortic valve stenosis. The patient underwent a robot‐assisted laparoscopic radical right nephrectomy and was diagnosed with intravenous lobular capillary hemangioma. Conclusion It is thought that surgical treatment is necessary to differentiate intravenous lobular capillary hemangioma from renal cell carcinoma in preoperative examinations.